2009
DOI: 10.1007/s10755-009-9119-y
|View full text |Cite
|
Sign up to set email alerts
|

Launching Interdisciplinary Programs as College Signature Areas: An Example

Abstract: Increasingly administrators are concerned with inspiring and supporting faculty members in the creation of interdisciplinary programs in response to research and funding shifts and public need. This article presents an initative undertaken at the University of Colorado Denver, demonstrating a method for identifying and launching a set of signature interdisciplinary programs for a diverse college environment that overcomes hesitancy and hindrances at the individual, departmental, and institutional levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Interdisciplinary methods move beyond multidisciplinary approaches where more than one discipline are involved but do not require faculty members to integrate their perspectives and create a different way of approaching complex issues (Stone et al 2009). Given that professors involved in interdisciplinary curriculum development come from different knowledge domains, their discipline-specific language or jargon often serves as a barrier to clear communication (White 2000).…”
Section: Interdisciplinary Curriculum Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Interdisciplinary methods move beyond multidisciplinary approaches where more than one discipline are involved but do not require faculty members to integrate their perspectives and create a different way of approaching complex issues (Stone et al 2009). Given that professors involved in interdisciplinary curriculum development come from different knowledge domains, their discipline-specific language or jargon often serves as a barrier to clear communication (White 2000).…”
Section: Interdisciplinary Curriculum Developmentmentioning
confidence: 99%
“…The literature also suggests that interdisciplinarity could be enhanced as faculty members move towards acquiring interactional expertise in other disciplines. Stone et al (2009) explained that a shift in discussion has occurred, moving from the benefits of interdisciplinary approaches to the question of how to develop such programs.…”
Section: Interdisciplinary Curriculum Developmentmentioning
confidence: 99%
“…Moreover, a number of subjects such as ethics cross disciplines. Society faces complex challenges that don't necessarily fall clearly into the silo of a single discipline (Stone et al 2009). Business schools have long been urged to concentrate on crossfunctional decision-making and to focus on the universal business student, not on the major, when delivering core content (Chonko 1993).…”
Section: Interdisciplinary Educationmentioning
confidence: 99%
“…Funding is competitive, so this alone could be a threat to resources and to positive collaboration (Kezar &Elrod, 2012 andStone et al, 2009). "Typically, resources and rewards are directed via a hierarchical organizational structure of departments, schools, and colleges" (Borrego et al, 2014, p. 859).…”
Section: Mission and Strategiesmentioning
confidence: 99%
“…"Unless all of most members share some fantasies in common ie., unless they have an organizational saga, both the members' commitment to the organization and their ability to create a cooperative communicative climate will be slight" (Bormann, 1982, p.58). For the long-term success of interdisciplinary programs, Stone et al (2009) found they should be integrated into the individual unit's mission allowing 'the program to function within the everyday workings of the institution and lessen marginalization.' "The mission statement of A & S is to improve life in the Commonwealth and particularly in the greater Louisville urban area, creating knowledge through its research, sharing knowledge through its teaching, and guiding and all its students to realize their potential.…”
Section: Mission and Strategiesmentioning
confidence: 99%